Evaluation of two diagnostic methods of scrub typhus with Bayes rule - Kabi, Shobhitendu; Das, Chandan; Rath, Siba N.; Panda, Baikuntha N.; Padhy, Rabindra N. (International Journal of Advances in Medicine, 2017)
Background: Scrub typhus or rickettsia, a zoonotic infection occurs due to the transmission of Gram-negative bacteria, Orientia tsutsugamushi and/or Tsutsugamushi sp. by the larval stage of the trombiculid mite, Leptotrombidium deliense. Infections at endothelial cells and phagocytes manifest clinically as vasculitis with an acute onset of fever, rashes, headache, myalgia, multiple organ dysfunction, eschar, respiratory morbidity, meningioencephalitis and sepsis syndrome on skin, whose severity varying with patients. Herein obtained data is used for evaluating the dependability of two determinative tests. Methods: The prospective survey with 80 rickettsia patients was carried during the last 6 months of 2016. Patients with the occurrence of fever for more than two days and a clinical suspicion of rickettsia infection were promoted for Weil-Felix as well as, ELISA tests. Results: The prevalence of rickettsia in the population of 80 patients was 17.5, and the sensitivity (the portion of the people with the rickettsia infection who will have positive Weil-Felix test results) value was 0.7143 and specificity (the people without the disease who will have negative Weil-Felix test results) value was 0.9697. Probability of Weil Felix test positive was 0.15, and probability of ELISA test positive was 0.175. Conclusions: The dependability of each test independently or a posteriori probability was 0.857. Both tests are dependable for correctness of outcomes being 0.857 or 85.7%, in combination; a high specificity value of Weil Felix test is a valuable test.